Comparison between Sublingual and Vaginal Misoprostol for Induction of Labour in Primigravida - Ghimire, Sailaja; Sharma, Deepanjali; Dhakal, Samjhana; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To compare the outcome and side effects of administration of sublingual misoprostol with vaginal misoprostol for induction of labour and cervical ripening.Methods: It was a hospital based comparative study which was carried out in 120 patients in each group of sublingual and vaginal route of misoprostol induction from August 2016 to February 2017 at Paropakar Maternity and Women’s Hospital, Thapathali, Kathmandu. Patients with Bishops score